Nurturing Democratic Citizenship Through Human Conversation. (1st October 2016) - Pickett, Brent L.; Kleinsasser, Audrey M.
Abstract: Responding to the increasing sophistication in the arts of deception in the public realm, the authors turn to Goodlad's ideal of democratic citizenship nurtured through human conversation in the classroom and development of critical skills to evaluate the accuracy of arguments .